BRG1 Links TLR4 Trans-Activation to LPS-Induced SREBP1a Expression and Liver Injury - Dong, Wenhui; Zhu, Yuwen; Zhang, Yangxi; Fan, Zhiwen; Zhang, Ziyu; Fan, Xiangshan; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Multiple organ failure is one of the most severe consequences in patients with septic shock. Liver injury is frequently observed during this pathophysiological process. In the present study we investigated the contribution of Brahma related gene 1 (BRG1), a chromatin remodeling protein, to septic shock induced liver injury. When wild type (WT) and liver conditional BRG1 knockout (LKO) mice were injected with lipopolysaccharide (LPS), liver injury was appreciably attenuated in the LKO mice compared to the WT mice as evidenced by plasma ALT/AST levels, hepatic inflammation and apoptosis. Of interest, there was a down-regulation of sterol response element binding protein 1a (SREBP1a), known to promote liver injury, in the LKO livers compared to the WT livers. BRG1 did not directly bind to the SREBP1a promoter. Instead, BRG1 was recruited to the toll-like receptor 4 (TLR4) promoter and activated TLR4 transcription. Ectopic TLR4 restored SREBP1a expression in BRG1-null hepatocytes. Congruently, adenovirus carrying TLR4 or SREBP1a expression vector normalized liver injury in BRG1 LKO mice injected with LPS. Finally, a positive correlation between BRG1, TLR4, and SREBP1a expression was detected in human liver biopsy specimens. In conclusion, our data demonstrate that a BRG1-TLR4-SREBP1a axis that mediates LPS-induced liver injury in mice.